MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU SISWA SATUAN PENDIDIKAN MUADALAH (SPM) ULYA MADRASAH DINIYYAH AL-AMIRIYYAH BLOKAGUNG - Nurkafidz Nizam Fahmi; Ahmad Shodiq Pratama (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this research is to describe and analyze curriculum management in terms of planning, implementation and evaluation at SPM Ulya Madrasah Diniyyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi. Second, to determine the role and function of curriculum management in improving the quality of students of SPM Mudalam Madrasah Diniyyah Al-Amiriyyah Tegalsari Banyuwangi. This study uses a qualitative approach method, data collection is carried out using interview, observation and documentation techniques, then the instrument used in this study is the human instrument (researcher as an instrument), then after data collection, the data obtained are field notes, speeches , and respondent's actions, documents, and others, then the data sources obtained in this study are developed during the research process. The result of this research is that the WKM SPM Muisah Ulya Madrasah Diniyyah Al-Amiriyyah Curriculum is holding an additional hours of study program that aims to complete the targets that have not been achieved and to reform curriculum management in terms of curriculum planning, implementation and evaluation.